Local Business Organization as Institutional Support for Local Entrepreneurship (Case Study) - GRZYMAŁA ZBIGNIEW; WÓJCIK-CZERNIAWSKA Agnieszka; JĘDRZEJEWSKI HIERONIM (Communications of International Proceedings, 2022)
This paper aims to present a case study for the concept of an institution as a local economic organization. This concept was a proposal to activate relations between the local government, entrepreneurs and other stakeholders at the local level within the commune, where local governments play a key role in these activities. Their activity plays a special role as an intermediary between all local stakeholders, in particular SMEs. The task was completed in 2 stages - research and implementation. The first one was carried out by the method of literature research and ended with the formulation of support instruments, and the second was based on questionnaires and interviews conducted in 20 selected pilot municipalities. Literature research on the existing mechanisms of cooperation between enterprises and local governments included in particular the identification of good practices in selected 16 countries. The second stage was carried out with the use of questionnaires and interviews, which included a diagnosis of the situation in selected communes, a proposal of a concept and their verification. The implementation of this sequence made it possible to formulate a thesis and verify the formulated research hypotheses. The research hypothesis assumed that initiating and undertaking activities activating the cooperation of local entrepreneurs with the local government influences the improvement of local entrepreneurship. An instrument for the implementation of these activities would be a formal organization in the form of a local economic organization. As a result of this hypothesis, it was assumed that increasing the effectiveness of cooperation between these stakeholders increases the level of local entrepreneurship.
Keywords: Institutions; New Institutional Economics; entrepreneurship; economic development; local government; local entrepreneurship organization; local stakeholders; formal and informal institution